Pediatric pedicle screw (In)accuracy based on postoperative computed tomography - Sahni, Deshdeepak; Prasad, Prashant; Hadley, Caroline; Tran, Brandon H.; Fulkerson, Daniel H.; Hwang, Steven W.; Jea, Andrew (Journal of Pediatric Neuroradiology, 2014)
Though pedicle screws are widely used in spinal stabilization, studies evaluating the variables affecting placement accuracy and effects of accuracy on outcome are limited. Using computed tomography (CT), we evaluated the accuracy of pedicle screw placement in pediatric and transitional patient populations. We evaluated screw placement in a series of 276 thoracic, lumbar, and sacral pedicle screws implanted in 41 patients with the assistance of fluoroscopy by a single surgeon at a single institution from September 1, 2007 to December 31, 2012. Postoperative CT was performed and each screw was graded based on relation to neurologic, osseous, and intra thoracic and intra-abdominal landmarks by an independent neuro radiologist: Grade I, entirely intra pedicular; Grade II, violates lateral pedicle but screw tip entirely within the vertebral body; Grade III, tip penetrates the anterior or lateral vertebral body; Grade IV, breaches medial or inferior pedicle; and Grade V, violates pedicle or vertebral body and threatens spinal cord, nerve root, or great vessels, requires immediate revision or removal. The accuracy rate (Grades I and II) was lower than expected (76.8%). Screw misplacements (Grades III, IV, and V) were numerous (23.2%), although the overall complication rate remained low. There was no statistically significant difference in pedicle screw accuracy as a function of surgeon experience, patient age, or patient diagnosis. This suggests the need for advanced intraoperative imaging, such as neuronavigation or CT, to aid placement of spinal instrumentation in the pediatric and transitional patient population. While postoperative CT should be considered gold standard for evaluating pedicle screw placement, further study is warranted to evaluate overall accuracy and assess the need for more extensive intraoperative imaging to improve accuracy.
Keywords: Pedicle screw; pediatric spine; computed tomography; pedicle screw accuracy